2007
DOI: 10.1002/pmic.200700163
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of the proteome of the mouse striatum

Abstract: Many diseases of the mammalian CNS, including Parkinson's (PD) and Lesch Nyhan disease (LND), are associated with programmatic neurodegeneration or dysfunction of dopaminergic neurons in the mesencephalon, the nigrostriatal pathway, and its projections in the striatum [1-4]. Proteomic studies on brain tissue of both animal models and human PD patients have provided evidence for dysfunction and damage of many pathways, including oxidative stress-related damage, ubiquitin-proteasome dysfunction, mitochondrial en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There are proteomic studies of fibroblasts from subjects who had dystonia related to defects in the ATP5F1E gene, 26 and proteomic studies of cerebrospinal fluid from subjects with inherited neurotransmitter defects 27 . Several studies also reported proteomic findings for cell or animal models of dystonia associated with the HPRT1 gene 28–31 . One study reported proteomics results for 3 cases with inherited dystonia from material sticking to electrodes used for mapping during deep brain stimulation surgery 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are proteomic studies of fibroblasts from subjects who had dystonia related to defects in the ATP5F1E gene, 26 and proteomic studies of cerebrospinal fluid from subjects with inherited neurotransmitter defects 27 . Several studies also reported proteomic findings for cell or animal models of dystonia associated with the HPRT1 gene 28–31 . One study reported proteomics results for 3 cases with inherited dystonia from material sticking to electrodes used for mapping during deep brain stimulation surgery 32 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies also reported proteomic findings for cell or animal models of dystonia associated with the HPRT1 gene. [28][29][30][31] One study reported proteomics results for 3 cases with inherited dystonia from material sticking to electrodes used for mapping during deep brain stimulation surgery. 32 Each of these studies revealed some abnormalities likely to be specific to the monogenic disorder studied or the type of sample used, so they are difficult to compare to results reported from the current study.…”
Section: Comparison With Related Studiesmentioning
confidence: 99%
“…AK-1 is a member of the AK family that plays a key role in homeostasis of purine metabolism and energy production and highly expressed in energy-intensive tissues such as brain and striated muscle and during neuron development. However, the study has not yet elucidated the nature of the functional striatal defect in HPRT deficiency [38].…”
Section: -D Gel Electrophoresis and 2-d Differential Gel Electrophormentioning
confidence: 99%
“…In particular, proteomic technologies have been also applied in the analysis of the substantia nigra derived from parkinsonian subjects [ 26 - 28 ]. On the other hand, MS-based qualitative proteomics has been employed to profile the murine striatum proteome and secretome [ 29 , 30 ]. However, despite these efforts to identify and catalogue part of the murine proteins present in BG, only a very limited number of human proteins have been characterized in these independent and functionally related substructures that compose the BG.…”
Section: Introductionmentioning
confidence: 99%